2018
DOI: 10.1097/mph.0000000000001145
|View full text |Cite
|
Sign up to set email alerts
|

Induction Dosage of Propofol for Repeated Sedations in Children With Hematological Disorders

Abstract: Pediatric patients with hematologic malignancies require several procedural sedations by means of propofol infusion. We retrospectively analyzed the medical records of leukemic pediatric patients who had undergone procedural sedations at an Italian tertiary referral center (San Gerardo Hospital, Monza) from January 2011 to November 2013. We retrieved the following: demographics; diagnosis; chemotherapy phase; use of corticosteroids; induction dosage of propofol, fentanyl and/or ketamine; and the type of proced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In a cohort of pediatric patients with hematologic malignancies, a previous study found that the induction dose of propofol had to be increased over time. 6 An obvious difference between that study and ours is that it evaluated propofol dose as the endpoint to evaluate tolerance, instead of evaluating a change in effect as we did in our study. In addition, the propofol dose was determined by the anesthesiologist in the previous study and this A B C FIGURE 1.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…In a cohort of pediatric patients with hematologic malignancies, a previous study found that the induction dose of propofol had to be increased over time. 6 An obvious difference between that study and ours is that it evaluated propofol dose as the endpoint to evaluate tolerance, instead of evaluating a change in effect as we did in our study. In addition, the propofol dose was determined by the anesthesiologist in the previous study and this A B C FIGURE 1.…”
Section: Discussionmentioning
confidence: 86%
“…Animal models show the development of acute tolerance to the hypnotic effect of propofol 2 but in pediatric patients, the findings have been mixed. [3][4][5][6] Gamma-aminobutyric acid (GABA) A receptor-dependent general anesthetic acts in the central nervous system (CNS) and leads to dose-dependent stereotypical changes in neural oscillations 7,8 that can be recorded noninvasively with an electroencephalogram (EEG). Analysis of the EEG in the frequency domain (ie, spectral analysis) is an increasingly popular method to understand the mechanism and effect of anesthetics on the brain.…”
mentioning
confidence: 99%
See 1 more Smart Citation